Determinants of latent tuberculosis infection among nurses at public health centers in Indonesia - Meira Erawati; Megah Andriany (Belitung Nursing Journal, 2022)
Background: The incidence of latent tuberculosis among healthcare workers, especially nurses, at public health centers in Indonesia has been increased. Therefore, factors related to the tuberculosis incidence need to be further investigated. Objective: This study aimed to identify the determinants of latent tuberculosis infection among nurses at public health centers in Indonesia. Methods: This non-experimental, cross-sectional study included 98 nurses. Data on the determinants of latent tuberculosis infection were collected using validated questionnaires, and the infection status was confirmed by Interferon Gamma Release Assay or IGRA test. Logistic regression was used for statistical analysis, with a significance level of p < 0.05. Results: Health facilities for tuberculosis transmission prevention were available in all public health centers (100%). Protocols for preventingtuberculosis transmission including occupational health and safety training (OR = 13.24, 95% CI [2.29–58.55]; p = 0.001), handwashing after contact with patients or specimens (OR = 20.55, 95% CI [4.23–99.93]; p = 0.000), and wearing of medical masks (OR = 9.56, 95% CI [1.99–45.69];p = 0.005) were found to be significant determinants of latent tuberculosis infection among nurses. Conclusion: The availability of protective equipment and implementation of health protocols among nurses at public health centers are the main determinants of latent tuberculosis infection. Hence, they should be maintained by all nurses to prevent the spread of tuberculosis.